The effect of crossword puzzle on the eighth grade students’ reading comprehension of descriptive text at SMPN 1 Barat Magetan - Agustin Noni Munawaroh; Lulus Irawati; Arri Kurniawan (Universitas PGRI Madiun, 2018)
The objective of this experimental research is to know whether or not there is an effect of using Crossword Puzzle on the Eighth grade students’ Reading Comprehension of Descriptive texts at SMP Negeri 1 Barat. The researcher uses design True-experimental research in sub design The Randomized Posttest-Only Control Group Design. This research uses random sampling. The data collection method is test. The researcher uses primary data consisted of the students’ scores collected by a Reading Comprehension. The researcher uses Pair-Sample t-test to know the result whether it was statistically significant. In research procedure the researcher uses planning, application, and reporting. The results of the research are that: (1) the procedures of teaching reading by using Crossword Puzzle consists of preparation and teaching and learning process. In preparation activities, the researcher prepares the material of descriptive text and RPP or lesson plan. In teaching and learning process, the researcher does three activities in two meetings. The first meeting, teaching a reading by using a conventional technique and the second meeting, by using a Crossword Puzzle. (2) The effect of using a Crossword Puzzle on the eighth grade students’ reading comprehension of the descriptive text at SMP Negeri 1 Barat is significant. It can be seen from the significant value (2-tailed) of that is 0.000. It is lower than 0.05. It means that the mean score of one class is different. The mean score of pretest is 55.7813 while the mean score of the post test is 96.7188. It means that a crossword puzzle is effective to teach a reading comprehension..